2014
DOI: 10.1007/s11051-014-2419-x
|View full text |Cite
|
Sign up to set email alerts
|

Dark field nanoparticle tracking analysis for size characterization of plasmonic and non-plasmonic particles

Abstract: Dark field microscopy is a widely unknown method to measure the particle size distribution of diffusing nanoparticles by particle tracking. Here we demonstrate that by using the surface plasmonic resonance of Au nanoparticles, size differences of ca. 20 nm can be identified within the particle size distribution. For that purpose, we developed a software tool which helps to analyze color videos of diffusing nanoparticles retrieved from CCD or CMOS cameras. Polystyrene beads with a diameter of 100 and 200 nm wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 25 publications
(33 reference statements)
0
53
0
Order By: Relevance
“…The bright-field approach provides much higher light throughput for dynamic imaging at the millisecond timescale compared to dark-field microscopy that suffers low light throughput. We have demonstrated that PANORAMA can size single nanoparticle down to 25 nm which exceeds the 100 nm dielectric particle detection limit achieved via dark-field microscopy 3 , dynamically monitor single nanoparticle approaching the plasmonic surface, and count individual nanoparticles in a cluster. PANORAMA would provide new capabilities in label-free imaging and single nanoparticle analysis.…”
Section: Discussionmentioning
confidence: 94%
“…The bright-field approach provides much higher light throughput for dynamic imaging at the millisecond timescale compared to dark-field microscopy that suffers low light throughput. We have demonstrated that PANORAMA can size single nanoparticle down to 25 nm which exceeds the 100 nm dielectric particle detection limit achieved via dark-field microscopy 3 , dynamically monitor single nanoparticle approaching the plasmonic surface, and count individual nanoparticles in a cluster. PANORAMA would provide new capabilities in label-free imaging and single nanoparticle analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Even if its use seems to be justified, no real influence is observed, and it can be explained by the localization error of the setup. Referring to the experimental data for 250 nm radius beads, the maximum displacement observed is 1.14 m, while the theory [ 35 ] gives: …”
Section: Results and Discussionmentioning
confidence: 99%
“…Dark field microscope images also confirm the size increase of NPs. The color change in Figure (from green to yellow) indicates the growth of NPs …”
Section: Resultsmentioning
confidence: 99%